Uneven Stripping Behavior, an Unheeded Killer of Mg Anodes. Issue 31 (3rd July 2022) - Liu, Xin; Du, Aobing; Guo, Ziyang; Wang, Chen; Zhou, Xinhong; Zhao, Jingwen; Sun, Fu; Dong, Shanmu; Cui, Guanglei
Abstract: Uniform magnesium (Mg) plating/stripping under high areal capacity utilization is critical for the practical application of Mg‐metal anodes in rechargeable Mg batteries. However, the failure of the Mg‐metal anode when cycling under a practical areal capacity (>4 mA h cm −2 ), is of rising concern. The mechanism behind these failures remains controversial. In this work, it is illustrated that the initial plating Mg can be undoubtedly uniform in a wide range of current densities (≤5 mA cm −2 ) and under a practical areal capacity (6 mA h cm −2 ). However, an unusual self‐accelerating pit growth is observed in the Mg stripping side under moderate current densities (0.1–1 mA cm −2 ), which severely deteriorates the anode integrity and subsequent Mg plating uniformity, causing failure of the Mg‐metal anode or short circuit of the battery. The stripping morphology depends on the applied current density, as non‐uniformity versus the current density displays a volcano plot during the stripping process. Through in situ spectroscopy, it is illustrated that this current‐dependent behavior is determined by the evolution of chlorine‐containing complex ions near the interface. This research reminds that the plating/stripping process of the Mg‐metal anode must be considered comprehensively for practical Mg‐metal batteries. Abstract : An astonishingly uniform electroplating morphology is proven under practical current density and areal capacity in rechargeable Mg batteries, and an asymmetric phenomenon between the plating and stripping processes is discovered. More critically, a nonlinear volcano relation between the non‐uniformity of the stripping morphology and the current density is proposed, which is defined by the distribution of chlorine‐containing complex ions at the interface.